Evaluating the performance of some basic skills by players of the Specialized Center for Gifted Care Football for ages 13-15 in Baghdad (Damu Journal of Sport Sciences, 2025)
It is necessary to track the progress of the players in order to complement their physical, skill, psychological, tactical and functional capabilities by relying on tests as one of the important indicators of the game of football, and identifying the level of performance of the players in the basic skills of any game indicates the general level of the team and knowing what it has reached and what remains to be achieved, This is what the researcher wants to achieve for the players of the Specialized Center for Talented Football in Baghdad, aged 13-15 years in Baghdad, The study aimed to identify the level of performance of some basic skills for the players of the National Center for Talented Football in Baghdad. To achieve this, the study was conducted on a sample of (28) players from the Specialized Center for Talented Football in Baghdad, The exploratory experiment was conducted on (4) players, and after completing the experiment, they were returned to the study. The researcher used the statistical package (SPSS) to process the data. The basic skills and their tests were also identified after presenting them to a group of experts, The researcher concluded and applied the tests and obtained results. The researcher converted them to standard levels and determined the percentages for each level of skills and concluded that the sample was at an average level or above, which shows the impact of the training units applied at the center on the research sample, The need to adopt an evaluation of the performance of the players of the Specialized Center for Talented Football Care in all Iraqi centers.